2018
DOI: 10.1007/s40618-018-0866-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of PON1 gene polymorphisms with polycystic ovarian syndrome risk: a meta-analysis of case–control studies

Abstract: Our study has shown that PON1 - 108 C/T polymorphism might be associated with increased risk of PCOS under the allelic, homozygote, heterozygote, and dominant models. Additionally, PON1 192 Q/R and L55M polymorphisms were significantly related only in the allelic and recessive model, and in the heterozygote and dominant model, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…GWAS has been carried out in Han Chinese and European ancestry women and reproduced identifying 16 loci ( Chen et al, 2011 , Shi et al, 2012 , Hayes et al, 2015 , Day et al, 2015 ). Meta-analysis studies performed in PCOS with molecular case-control studies have been documented with both positive and negative factors ( Cheng et al, 2019 , Li et al, 2020 , Liang et al, 2019 , Liao et al, 2018 , Liu et al, 2017 , Liu and Fat, 2017 , Niu et al, 2018 , Pabalan et al, 2016 , Park et al, 2019 , Tiongco et al, 2019 , Zhu et al, 2019 , Zou et al, 2019 ). Day et al ( Day et al, 2018 ) from his large meta -analysis and GWAS studies; identified three novel loci such as PLGRKT ; ZBTB16 and MAPRE1 and also replication of 11 loci previously documented.…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…GWAS has been carried out in Han Chinese and European ancestry women and reproduced identifying 16 loci ( Chen et al, 2011 , Shi et al, 2012 , Hayes et al, 2015 , Day et al, 2015 ). Meta-analysis studies performed in PCOS with molecular case-control studies have been documented with both positive and negative factors ( Cheng et al, 2019 , Li et al, 2020 , Liang et al, 2019 , Liao et al, 2018 , Liu et al, 2017 , Liu and Fat, 2017 , Niu et al, 2018 , Pabalan et al, 2016 , Park et al, 2019 , Tiongco et al, 2019 , Zhu et al, 2019 , Zou et al, 2019 ). Day et al ( Day et al, 2018 ) from his large meta -analysis and GWAS studies; identified three novel loci such as PLGRKT ; ZBTB16 and MAPRE1 and also replication of 11 loci previously documented.…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…All 21 systematic reviews included a meta-analysis and were based on case-control or cross-sectional primary studies. Nineteen systematic reviews investigated SNPs [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. The remaining two systematic reviews investigated CAG repeat length or tandem repeats respectively [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two systematic reviews investigated CAG repeat length or tandem repeats respectively [52,53]. Candidate genes focused on three main aspects of PCOS pathophysiology: metabolic dysfunction, [33,35,38,39,40,41,42,43,44,48,49,50,52], imbalances in androgens and gonadotrophins [36,37,51,53], and inflammation [34,45,46,47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations